Hepatoprotective Effects of Ixora parviflora Extract against Exhaustive Exercise-Induced Oxidative Stress in Mice - Chi-Chang Huang; Hsiu-Mei Chiang; Kuo-Ching Wen; Chih-Yang Huang; Wan-Teng Lin; Wen-Ching Huang; Nai-Wen Kan; Mei-Chich Hsu (Molecules, 2013)
Ixora parviflora, a species of the Rubiaceae, is rich in polyphenols and flavonoids, and has been traditionally used as a folk medicine. An I. parviflora extract (IPE) has great antioxidant activity in vitro, including a scavenging effect on superoxide radicals, reducing power, and ferrous ion-chelating ability. However, whether IPE is efficacious against oxidative damage in vivo is not known. The purpose of this study was to determine the protective effects of IPE treatment on hepatic oxidative stress and antioxidant defenses after exhaustive exercise in mice. Fifty male C57BL/6 mice (6 week old) were randomly divided into five groups and designated a sedentary control with vehicle (C), and exhaustive exercise with vehicle (IPE0), low dosage (IPE10), medium dosage (IPE50) and high dosage (IPE100) of IPE at 0, 10, 50, and 100 mg/kg, respectively. After a single bout of exhaustive swimming exercise challenge, levels of blood ammonia and creatine kinase (CK), and hepatic superoxide dismutase (SOD) protein expression, thiobarbituric acid-reactive substance (TBARS), and gp91phox, p22phox, and p47phox subunits of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase expressions in the IPE0 group were significantly affected compared to those of the C group, but they were all significantly inhibited by the IPE treatments. Results of the present in vivo study in mice indicate that I. parviflora extract possesses antioxidative and hepatoprotective potential following exhaustive exercise.